Arabidopsis thaliana Uncoupling Proteins (AtUCPs): insights into gene expression during development and stress response and epigenetic regulation - Nogueira, Fabio Tebaldi Silveira [UNESP]; Sassaki, Flavio Tetsuo [UNESP]; Maia, Ivan de Godoy [UNESP] (Springer/plenum Publishers, 2011)
Mitochondrial inner membrane uncoupling proteins (UCP) catalyze a proton conductance that dissipates the proton electrochemical gradient established by the respiratory chain, thus affecting the yield of ATP synthesis. UCPs are involved in mitochondrial energy flow regulation and have been implicated in oxidative stress tolerance. Based on the global gene expression profiling datasets available for Arabidopsis thaliana, in this review we discuss the regulation of UCP gene expression during development and in response to stress, and provide interesting insights on the possible existence of epigenetic regulation of UCP expression.
Keywords: Uncoupling proteins; Gene expression; Stress; Development; Arabidopsis